Brief Communication on Parents’ Perception towards Favourite Play Equipment, Satisfaction Level and Safety of Public Climbing Equipment in Malaysia - Kah Ling, Cheah; Ahmad Azmeer, Raja; Shahrizal Dolah, Mohd; Hasley, Saiful; Bolong, Jusang (International Journal of Engineering and Technology, 2018)
Public playground injuries caused by unsafe climbing equipment is a public health concern. This study aims to measure Malaysian parentsâ€™ perception towards their childrenâ€™s favourite play equipment and satisfaction level on public equipment safety. A self-administered survey was employed among 50 Malaysians citizen, aged between 18 to 45 years. Data was descriptively analysed using SPSS version 21.0. The results showed that climbing equipment was favourite playing equipment among children. Furthermore, our study revealed that (90%) of parents were dissatisfied with public climbing equipment. We found that while (92%) of the parents agreed that safety levels of the climbing equipment should be improved. In addition, the study revealed that more than three quarters of respondents agreed to reduce free fall height, improve product materials, focus on reducing falls, and implement effective safety inspection including regular maintenance to improve the safety level of public climbing equipment. Results from this study could assist in advanced urban recreation safety for controlling injuries and regain parentsâ€™ trust on playground safety.Â Â